The Association of Nutritional Risk Screening 2002 With 1-Year Re-hospitalization and the Length of Initial Hospital Stay in Patients With Heart Failure - Chen, Zhezhe; Jiang, Hangpan; He, Wujian; Li, Duanbin; Lin, Maoning; Wang, Min; Shang, Min; Zhang, Wenbin (Frontiers in Nutrition, 2022)
Backgrounds and Aims: Nutritional Risk Screening 2002 (NRS-2002) has been widely recommended for identifying the nutritional risk. However, the association between NRS-2002 and the prognosis of heart failure has not been fully addressed. This study aimed to explore the association of NRS-2002 with one-year re-hospitalization and the length of initial hospital stay in heart failure patients. Methods: This retrospective study included 2,830 heart failure patients. The primary endpoint was one-year re-hospitalization for heart failure. The secondary endpoint was the length of initial hospital stay. Log-binomial regression analysis was performed to determine the association between NRS-2002 and re-hospitalization. Cox regression model was fitted to estimate hazard of discharge. The cumulative incidence curves of discharge were plotted using Kaplan-Meier method and log rank test was performed. Exploratory analysis was also conducted according to the classification of heart failure and the level of N-terminal pro-B-type natriuretic peptide (NT-proBNP) fold-elevation. Results: Among 2,830 heart failure patients, the mean age was 64.3 years and 66.4% were male. 122 (4.3%) patients were considered at high nutritional risk. Log-binomial regression analysis demonstrated that higher NRS-2002 score was an independent risk factor of re-hospitalization ([1 vs. 0]: RR=1.383, 95% CI=1.152 to 1.660; [2 vs. 0]: RR=1.425, 95% CI=1.108 to 1.832; [3-7 vs. 0]: RR=1.770, 95% CI=1.310 to 2.393). Kaplan-Meier curve showed that the cumulative incidence of discharge was lower in high nutritional risk group (Log rank P <0.001). Cox regression analysis also found that higher NRS-2002 score (2 or ≥3) was strongly associated with longer length of initial hospital stay ([2 vs. 0]: HR=0.854, 95% CI=0.748 to 0.976; [3-7 vs. 0]: HR=0.609, 95% CI=0.503 to 0.737). Exploratory analysis showed that such association still remained irrespective of NT-proBNP fold-elevation, but only existed in patients with HFpEF. Conclusion: In patients with heart failure, high NRS-2002 score was strongly and independently associated with the incidence of one-year re-hospitalization and the length of initial hospital stay.